Case Report: Abnormal ECG in a Patient With Acute Pancreatitis - Long, Yunxiang; Tang, Manyun; Wang, Jie; Liu, Hui; Jian, Zhijie; Li, Guoliang; Liu, Chang (Frontiers in Cardiovascular Medicine, 2021)
Background: Both acute pancreatitis and acute myocardial infarction (AMI) are rapidly progressive and frequently fatal diseases that can be interrelated and lead to a vicious cycle for further problems. The concomitant occurrence of AMI and acute pancreatitis is rare but critical, and efficient diagnosis and treatment of such patients are challenging. Case summary: We reported an uncommon case of abnormal ECG findings in a 63-year-old woman with acute pancreatitis. The patient exhibited increased biomarkers of myocardial injury, such as creatine kinase-MB and troponin T, as well as ST segment elevation in inferior leads II, III, and aVF. Both of these have been previously observed in patients with acute abdomen in the absence of ST segment elevation myocardial infarction (STEMI), including pancreatitis. In addition, lacking complaints of chest pain or tightness was also supportive of this idea. Echocardiography indicated abnormalities in the functioning of the left inferior posterior wall segments and decreased overall systolic function of the left ventricle with a 51% ejection fraction. Eventually, AMI was diagnosed after coronary computed tomography angiography (CCTA) showing critical stenosis of the right coronary artery and left anterior descending artery segments. The patient was urgently transferred to the intensive care unit and was treated with anticoagulation, antiplatelet aggregation, lipid-lowering and other palliative drugs. Conclusion: Concomitant acute pancreatitis and AMI are often considered to be critical conditions with a poor prognosis. Therefore, it is important to rapidly identify this condition and consider transferring patients for multidisciplinary supportive care.